"That market has no quality": Performative place frames, racialisation, and affective re‐inscriptions in an outdoor retail market in Amsterdam. Issue 2 (16th December 2021) - van Eck, Emil
Abstract: This paper interrogates the performative and affective aspects of relational place‐making processes by which people construct the everyday geographies of public space. Based on ethnographic fieldwork in and around an outdoor retail market in Amsterdam, the research findings show that the hegemonic frame of this public space is deeply racialised, mediating the way in which traders, market managers, and visitors encounter one another on a daily basis. By drawing on a shift from a discursive conception of relational place‐making to a performative and affective one, the results show how racialised place frames come into being through day‐to‐day performative practices, and how this is confirmed and brokered by people confronted with racialised place discourses. The findings on traders social networks through which they sustain access to public space highlight the importance of attending to the affective dimensions of place‐making in academic work focused on place politics. Abstract : This paper interrogates the performative and affective aspects of relational place‐making processes by which people construct the everyday geographies of public space. Based on ethnographic fieldwork in and around an outdoor retail market in Amsterdam, the research findings show how market traders confirm and broker racialised place discourses.